Mg‐Pillared LiCoO2: Towards Stable Cycling at 4.6 V. Issue 9 (4th January 2021) - Huang, Yangyang; Zhu, Yongcheng; Fu, Haoyu; Ou, Mingyang; Hu, Chenchen; Yu, Sijie; Hu, Zhiwei; Chen, Chien‐Te; Jiang, Gang; Gu, Hongkai; Lin, He; Luo, Wei; et al.
Abstract: LiCoO2 is used as a cathode material for lithium‐ion batteries, however, cationic/anodic‐redox‐induced unstable phase transitions, oxygen escape, and side reactions with electrolytes always occur when charging LiCoO2 to voltages higher than 4.35 V, resulting in severe capacity fade. Reported here is Mg‐pillared LiCoO2 . Dopant Mg ions, serving as pillars in the Li‐slab of LiCoO2, prevent slab sliding in a delithiated state, thereby suppressing unfavorable phase transitions. Moreover, the resulting Li‐Mg mixing structure at the surface of Mg‐pillared LiCoO2 is beneficial for eliminating the cathode‐electrolyte interphase overgrowth and phase transformation in the close‐to‐surface region. Mg‐pillared LiCoO2 exhibits a high capacity of 204 mAh g −1 at 0.2 C and an enhanced capacity retention of 84 % at 1.0 C over 100 cycles within the voltage window of 3.0–4.6 V. In contrast, pristine LiCoO2 has a capacity retention of 14 % within the same voltage window. Abstract : The endeavor to deliver a high specific capacity for a LiCoO2 cathode at a voltage larger than 4.35 V is challenging. The deliberately introduced Mg ions at the Li layer of LiCoO2 endow this promising cathode with high capacity (204 mAh g −1 ) and excellent cycling stability and rate capability within a voltage window of 3.0–4.6 V.